Spirapril effectiveness and organo-protection in patients with metabolic syndrome and arterial hypertension - V. E. Oleynikov; A. S. Gerasimova; I. B. Matrosova; Yu. A. Tomashevskaya (Российский кардиологический журнал)
In this 24-week study, spirapril antihypertensive effect and organo-protection was assessed inpatients with metabolic syndrome (MS) and arterial hypertension (AH). Parameters of 24-hour blood pressure (BP) monitoring (systolic and diastolic BP - 24 hours, daytime, nighttime) and pulse BP were significantly higher in MS patients than in AH individuals. Seventy-five per cent of MS patients had pathological circadian BP profile, with non-dippers' prevalence. In the same group, more advanced target organ pathology was observed (left ventricular hypertrophy, increased vascular stiffness, microalbuminuria). Spirapril therapy was associated with target BP level achievement, circadian BP profile normalization, target organ pathology regression, and was potentially linked to insulin resistance reduction. Therefore, spirapril can be recommended for MS treatment, as well as for preventing target organ damage in MS and AH.